PEMBANGUNAN HUKUM YANG HUMANIS TEOSENTRIK (Eksistensi Nilai lslam Dalam Pembangunan Hukum Di Indonesia Pada Era Globalisasi Dan Transformasi Global) - Muhyidin, Muhyidin (Diponegoro Private Law Review, 2018)
Secularization of the norms of life is already a social reality, including the law in it. The belief in the emergence of globalization and global transformation as if new religions apart from the criticism of them included in every realm of human life. Therefore legal development will not be valid if it does not try to link it to the process of globalization and global transformation. While the time of religion is considered by some circles (law) unable to provide answers to the development of society in this century. Theocentric humanist development of law is an antithesis of secular development, which tries to offer a legal concept by not denying the existence of God in this life.   Keywords: Globalization & Global Transformation, Theocentric Humanism